ON CONTINUITY OF MULTIVALUED MAPPINGS - Khachatryan, A. R.; Khachatryan, R. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
The problem of continuity of multivalued mappings plays a great role in parametrical problems of optimization and in theory of differential inclusion. The article studies the problem of continuity of some multivalued mappings, which are given by inequalities and equations. The article also provides sufficient conditions, under which the intersection of multivalued mappings is a continuous multivalued mapping too.
Keywords: multivalued mappings; differential inclusion; parametrical problems; sufficient conditions